DEVELOPING STUDENTS ’PHYSICAL QUALITIES TO THE BENEFIT OF THEM - Uraimov Sanjar; Asqarova Nargiza (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article provides information on the qualities and abilities of physical culture, their manifestation, development and types of activities that require a clear regime for the proper organization and conduct of training